العربية في الكلمات التعبيري وتعريب الدخيل - Abdul Ghofur (Al-Fusha : Arabic Language Education Journal, 2020)
This topic, based on the claim, that reaching the goals of obtaining the flag in particular the Arabic language from the breadth of language. It is also known that the spread of Arabic in the expression (tandem and common verbal and antibodies) and the Arabization of the intruder there are the opinions of scientists in the phenomenon of occurrence in the language, some of them said the occurrence in the language, some of whom denied the occurrence. Based on this, the objectives of this research are: To learn about the breadth of Arabic in the expression (tandem and joint verbal and antibodies) and Arabization of the intruder, and to know the views of scientists in the phenomenon of Asa in this expression.